Effect of Lead (Pb) exposure towards green microalgae (Chlorella vulgaris) on the changes of physicochemical parameters in water. - Cheng Wan Hee; Wong Ling Shing; Chong Kah Chi (South African Journal of Chemical Engineering, 2021)
The release of pollutant such as lead (Pb) from factories, agriculture wastes, and domestic wastes into the environment has threatened the freshwater ecosystem. Therefore, there is a crucial need for a quick and efficient method for early detection of Pb in the aquatic environment. The aim of this study is to determine the changes of physicochemical parameters (pH, conductivity and dissolve oxygen) in the surrounding water body caused by Chlorella vulgaris that were exposed to Pb, as a mean of Pb bio-detection. The microalgae were exposed to different concentrations of Pb (1, 0.1 and 0.01 mg/L) and for each exposure, the physicochemical parameter changes in the surrounding water body were recorded at 0 hour (initial exposure), 1 hour, 2 hours, 6 hours and 24 hours by using the portable multiparameter meter. The results showed that the pH values of the water decreases as the concentration of metal exposure increases. On the other hand, the conductivity and dissolved oxygen showed a decreased in their values as the exposure time increases. This phenomenon could be attributed to the inhibition of the photosynthesis by the C. vulgaris as well as the ability of the algae to accumulate Pb and thus lowering the physicochemical parameters. Therefore, C. vulgaris serves as a good bioindicator for Pb pollution.